Mastro: a formação do Movimento dos Agricultores Sem Terra do Oeste do Paraná (1970-1990) - Moraes Junior, Leozil Ribeiro de (2011)
This work seeks to understand the processes that made possible the organization of individuals in social movements that struggle for land in western Parana, in the 70 and 80. The study of the Movement of Landless Farmers in the West of Paraná (Mastro) deconstructs prospects subject only posing as leaders and / or organizational entities such as unions, churches and parties. Or, the modernization of agriculture policies that excluded thousands of families from their small holdings and possessions. Thus, following and interpreting the speech of those who were part of the process, sought to counter the notion that use the memories of the subject only as a complement and illustration of bibliographies, those seen as the only ways to build political and historiographical positions. The research points to the importance of Mast for the constitution of the MST, reveals a number of important sources and discusses the issue of concentration of land ownership in western Paraná. Try to go through class debates and conflicts that have been established within the Mast, and indicates the class consciousness of these groups